Acute Kidney Injury Due to Systemic Absorption of Antibiotics Impregnated in a Bone Cement Spacer: An Underrecognized Complication of a Common Intervention. Issue 5 (September 2018) - Nakasone, Trisha S.; Multani, Ashrit; Chary, Aarthi; Renault, Cybele A.; Winslow, Dean L.
Abstract : Abstract: We report a case of acute kidney injury due to systemic absorption of tobramycin, gentamicin, and vancomycin from an antibiotic-impregnated cement spacer placed during revision of an infected total knee arthroplasty. The continual systemic antibiotic absorption and resultant nephrotoxicity required spacer removal, with subsequent improvement in renal function. Abstract : Acute kidney injury may occur due to systemic absorption of tobramycin, gentamicin, and vancomycin from antibioticimpregnated cement spacers placed during revision of infected total knee arthroplasties. The continual systemic antibiotic absorption and resultant nephrotoxicity may require spacer removal for subsequent improvement in renal function.